Study of Lipid Profile in Obese Individuals and the Effect of Cholesterol Lowering Agents on Them - Surajit Kumar Mukhopadhyay (Al Ameen Medical College, 2012)
Objectives: To study the effect of cholesterol lowering agents on lipid profile in obese patients. Background: Obesity leads to morbidity as well as mortality. There is usually increased level of total cholesterol, LDL- cholesterol, VLDL- cholesterol, triglycerides and decreased level of HDL- cholesterol in obesity. These are the risk factors for cardiovascular disease, hypertension, diabetes mellitus, pulmonary disorder and gall stones. Method: Thirty obese patients received treatment with Lovastatin along with dietary measures, compared with age and sex matched controls- before and after 6 weeks of therapy, presented in a table and results were analysed using student's "t" test (both paired and unpaired). Result: There was significant reduction in total cholesterol as well as LDL- cholesterol; HDL- cholesterol was also increased significantly. But triglycerides and VLDL- cholesterol showed small but significant increase. Conclusion: Cholesterol lowering agents like Lovastatin was quite effective when used long-term in dyslipidaemia in obesity towards reduction of risk factors for cardiovascular diseases, strokes, etc. Hypertriglyceridaemia should also be treated adequately